Bezoar-related stercoral perforation in an 11-year old child: Has anyone seen my other sock? - John D. Rutkoski; George K. Gittes (Elsevier, 2015)
Bezoars are accretions of indigestible material that develop within the gastrointestinal tract and occur with relative infrequency. Rarer yet, stercoral perforations of the colon (SPC) result from pressure-induced ischemia and are nearly universally associated with chronic constipation. We report only the second recorded case of a bezoar-related stercoral perforation of the colon, the first to result from ingestion of cloth, and the first in a pediatric patient.